Nights below Foord Street literature and popular culture in postindustrial Nova Scotia - Thompson, Peter 1981- (McGill-Queen's University Press, 2019)
"According to its licence plates, tourist brochures, and commercials, Nova Scotia is Canada's Ocean Playground--an idyllic vacation spot brimming with traditional cultural experiences. Yet this picturesque and welcoming ad-friendly façade overlooks the province's history of industrial development, the impact of resource extraction on its landscape, and the effects of its painful and still unfinished period of deindustrialization. Recounting Nova Scotia's struggle to come to terms with its extractive and industrial past, Nights below Foord Street focuses on the spaces ignored by the province's annual Doers and Dreamers tourist guide. Drawing on literary texts by Lynn Coady, Leo McKay, Sarah Mian, and Jonathan Campbell, popular television shows such as Trailer Park Boys, and films including Blackbird, Cottonland, and Poor Boy's Game, Peter Thompson examines the ways in which contemporary authors, filmmakers, and artists explore the lingering consequences of the boom-and-bust cycles of mining and manufacturing. As he demonstrates, these narratives depict a legacy of environmental exploitation, pollution, intermittent disasters, and labour violence left behind by the industrial era, all of which contrast starkly with the romantic and nostalgic portrait of Nova Scotia's industrial heritage promoted in museums, monuments, and tourist sites. As Donald Trump and other populist politicians appeal to working-class nostalgia and international attention converges on environmental racism in northern Nova Scotia, Nights below Foord Street intervenes into debates over the cultural and social effects of the post-industrial economy."--
Keywords: Geschichte 1990-2019; Massenkultur; Englisch; Nova Scotia -- Motiv; Literatur; Nova Scotia; Canadian literature / Nova Scotia / History and criticism; Canadian literature / 21st century / History and criticism; Popular culture / Nova Scotia; Deindustrialization / Nova Scotia; Nova Scotia / In popular culture; Canadian literature (English) / Nova Scotia / History and criticism; Canadian literature (English) / 21st century / History and criticism; Littérature canadienne-anglaise / Nouvelle-Écosse / Histoire et critique; Littérature canadienne-anglaise / 21e siècle / Histoire et critique; Culture populaire / Nouvelle-Écosse; Désindustrialisation / Nouvelle-Écosse; Nouvelle-Écosse / Dans la culture populaire; Canadian literature; Deindustrialization; Popular culture; 2000-2099; Criticism, interpretation, etc